(untitled) (Ameghiniana, 2014)
An Upper Permian gymnospermous wood from the Cerro Colorado de La Antigua (La Rioja province) is described. It is characterized by a little lobulated heterogeneous parenchymatic/sclerenchymatic pith; the primary xylem has wedge-like projections, and the secondary xylem is of Araucarioxylon type with marked growth rings. It is a "cornplaisant" wood.